Mechanistic insights into boron-catalysed direct amidation reactions. Issue 4 (19th January 2018) - Arkhipenko, Sergey; Sabatini, Marco T.; Batsanov, Andrei S.; Karaluka, Valerija; Sheppard, Tom D.; Rzepa, Henry S.; Whiting, Andrew
Abstract : The generally accepted monoacyloxyboron mechanism of boron-catalysed direct amidation is brought into question in this study, and new alternatives are proposed. Abstract : The generally accepted monoacyloxyboron mechanism of boron-catalysed direct amidation is brought into question in this study, and new alternatives are proposed. We have carried out a detailed investigation of boron-catalysed amidation reactions, through study of the interaction between amines/carboxylic acids and borinic acids, boronic acids and boric acid, and have isolated and characterised by NMR/X-ray crystallography many of the likely intermediates present in catalytic amidation reactions. Rapid reaction between amines and boron compounds was observed in all cases, and it is proposed that such boron–nitrogen interactions are highly likely to take place in catalytic amidation reactions. These studies also clearly show that borinic acids are not competent catalysts for amidation, as they either form unreactive amino-carboxylate complexes, or undergo protodeboronation to give boronic acids. It therefore seems that at least three free coordination sites on the boron atom are necessary for amidation catalysis to occur. However, these observations are not consistent with the currently accepted 'mechanism' for boron-mediated amidation reactions involving nucleophilic attack of an amine onto a monomeric acyloxyboron intermediate, and as a result of our observations and theoretical modelling, alternative proposed mechanisms are presented for boron-mediated amidation reactions. These are likely to proceed via the formation of a dimeric B–X–B motif (X = O, NR), which is uniquely able to provide activation of the carboxylic acid, whilst orchestrating the delivery of the amine nucleophile to the carbonyl group. Quantum mechanical calculations of catalytic cycles at the B3LYP+D3/Def2-TZVPP level (solvent = CH2 Cl2 ) support the proposal of several closely related potential pathways for amidation, all of which are likely to be lower in energy than the currently accepted mechanism.